Capital income taxation and specialization patterns: Investment tax vs. saving tax - Yoshiyasu Ono; Akihisa Shibata (Osaka University, Institute of Social and Economic Research (ISER), 2006)
Unless free international lending/borrowing is allowed, domestic saving equals domestic investment and hence saving and investment taxes have the identical effect, as is the case in a closed-economy context. However, if it is allowed, households can accumulate foreign assets besides domestic capital and hence saving and investment are separated, causing the two taxes to have different effects. Using a two-sector growth model, we show that the two taxes generate completely different effects on industrial structure. The investment tax always shrinks the capital-intensive sector whereas the saving tax may well expand it.
Keywords: F41; E62; 330; saving tax; investment tax; two-sector growth model; industrial structure; financial asset trade; Kapitalertragsteuer; Kapitalmobilität; Steuer; Mehr-Sektoren-Modell; Neue Wachstumstheorie